Peran Komunikasi dalam Meningkatkan Partisipasi Masyarakat pada Proyek Pembangunan Pedesaan Studi Kasus Desa Lembur Kecamatan Kota Komba Kabupaten Manggarai Timur - Andreas Watu; Imam Mukti; Erniwati Erniwati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The purpose of this study was to analyze how effective communication strategies can influence community participation in rural development projects and to identify factors that influence communication success in the local context. The research method used is a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and document analysis related to development projects. Respondents in this study included community members, local stakeholders, and parties involved in project implementation. The results showed that transparent, participatory, and sustainable communication had a significant impact on the level of community participation. Factors such as the active involvement of community leaders, the use of local media, and the existence of discussion forums also influenced the effectiveness of communication. In addition, this study found that two-way communication and involving the community in the planning and decision-making process increased the sense of ownership and support for development projects. The conclusion of this study is that a good communication strategy can significantly increase community participation in rural development projects. Recommendations for the implementation of communication strategies include increasing community involvement from the planning stage, utilizing local communication media, and developing effective feedback mechanisms. This study contributes to the understanding of the role of communication in rural development and can be a reference for planning similar projects in the future.